ANALYSIS OF EDUROAM-WIRELESS-INTERNET-SERVICE'S COVERAGE USING THE CONCEPT OF BUILDING INFORMATION MODELING (BIM) (CASE STUDY : 2ND FLOOR OF LABTEK IX-C ITB GANESHA CAMPUS) - Vandita, Gilang
Wireless internet networks / Wi-Fi is commonly used because of its practicality and convenience. However, there are often connectivity issues when connecting or about to connect to the device. Building Information Modeling (BIM) can be a solution to find out what factors might influence the connectivity. BIM is an accurate representation of an object in digital form. It can also embed spatial and non-spatial information as needed. The purpose of this research is to determine the factors that might affect Wi-Fi connectivity, in this case related to the influence of room layout, especially in the research area including the Lobby, R. 3101, and R. 3102 at Labtek IX-C through BIM modeling. The data used in this research are point clouds from TLS as a reference in object modeling and Wi-Fi signal strength test data. The steps and methods used in point cloud data processing include filtering, georeference, registration, and 3D modeling based on object-oriented. A review is also carried out regarding to object-oriented data structure. Then the database was also created and organized to combine the results of 3D object modeling with Wi-Fi signal strength data. After that, the integration results are displayed in the form of color visualization. The results of this research obtained in the form of a 3D model of the research area and the coverage of the Wi-Fi signal. Modeling is done based on object or object-oriented, where this method has a special data structure. The 3D model is equipped with color visualization for ease of analysis. From these results, it can be analyzed that room layout can affect the Wi-Fi connectivity received by the device. More specifically, the distance from the device to the router and the presence/absence of obstructions between the two can reduce the quality of the Wi-Fi signal strength received by the device.